The Bible, the Jews, and the death of Jesus: a collection of Catholic documents (United States Conference of Catholic Bishops, 2004)
Statements of the second Vatican Council and the Pontifical Biblical Commission. Nostra Aetate : declaration on the relationship of the Church to non-Christian religions, no. 4 (1965) ; The historical truth of the Gospels (1964) ; The interpretation of the Bible in the Church (1993) ; The Jewish people and their sacred scriptures in the Christian Bible (2002) -- Statements of Pope John Paul II. Address at the Great Synagogue of Rome (1986), no. 4 ; Address to Pontifical Biblical Commission (1997) -- Statements of the Pontifical Commission for Religious Relations with the Jews. Guidelines and suggestions for implementing the conciliar declaration Nostra Aetate, no. 4 (1974) ; Notes on the correct way to present the Jews and Judaism in preaching and catechesis in the Roman Catholic Church (1985) ; We remember : a reflection on the Shoah (1998) -- Statements of the United States Conference of Catholic Bishops. Guidelines for Catholic-Jewish relations (1967) ; Statement on Catholic-Jewish relations (1975) ; God's mercy endures forever : guidelines on the presentation of Jews and Judaism in Catholic preaching (1988) ; Criteria for evaluation of dramatizations of the passion (1988) -- Appendix. Catechism of the Catholic Church, nos. 595-598 ; John Paul II, Good Friday liturgy, April 10, 1998 ; Gospel narratives of the passion